Preservation of single human hearts from archaeological and historical contexts - D'Anastasio, Ruggero; Di Felice, Arianna; Cilli, Jacopo; Ripari, Patrizio; Speranza, Lorenza; Franceschelli, Sara; Capasso, Luigi (Medicina Historica, 2023)
The work analyzes a series of cardiac remains from archaeological and historical con-texts, from different periods and from different parts of the world. They have undergone an often natural conservative process, facilitated by certain environmental conditions, sometimes artificial, with the precise desire to give individual importance to the heart. The analysis of these hearts is mainly aimed at the presence or absence of pathological aspects present in each of them and focuses attention on the scientific and medical importance that can also be found in organic remains from contexts of this type.